Hiroshima, Nagasaki. 40 anos depois, lutar pela paz contra as armas nucleares - Rafael, Carlos (MNANP (Movement Against Nuclear Weapons in Portugal), 1985)
Illustration of mushroom cloud with red circle in its centre, in reference to the Japanese flag; skull on top of cloud Suggested translation: Hiroshima, Nagasaki. 40 years later, struggle for peace and against nuclear weapons PO-1916